Near‐infrared optical constants of naturally occurring olivine and synthetic pyroxene as a function of mineral composition. Issue 4 (12th April 2013) - Trang, David; Lucey, Paul G.; Gillis‐Davis, Jeffrey J.; Cahill, Joshua T. S.; Klima, Rachel L.; Isaacson, Peter J.
Abstract : [1] Radiative transfer theory will assist in determining olivine and pyroxene proportions and compositions from the surface of a planetary body composed of intimately mixed minerals. In order to use radiative transfer techniques, the model requires the optical constants of olivine and pyroxene. Optical constants are parameters that describe the degree light absorbed ( k ) and refracted ( n ) in a medium. Here we only parameterize k in the near infrared from 0.6 to 2.5 µm of natural olivine as a function of forsterite number and synthetic pyroxene with respect to wollastonite and ferrosilite number. In contrast to previous work, this study is an improvement on previous work because we have a diverse and larger sample size leading to robust optical parameters. Additionally, we characterize each k ‐spectrum with the modified Gaussian model (MGM). MGM is a physically realistic model of near‐infrared absorptions due to electronic transitions. In each spectrum, we model each absorption and continuum with Gaussians and an inverse of a linear function, respectively. We find that our fitting routine characterizes the olivine and pyroxene k ‐spectra in a robust and consistent manner. Then we use regression analysis to characterize each parameter of the Gaussians and the continuum as a function of mineral composition. The developed optical parameters from this work will allow calculations of mineral proportions and compositions on planetary surfaces with use of data from missions such as Dawn, MESSENGER, SELENE, and Chandrayaan‐1. Key Points: We characterize the optical constants of olivine and pyroxene. The optical parameters are described with respect to Fo, Fs, and Wo number. The optical parameters were tested against a meteorite and a lunar sample.